Development of infrared staking process for an automotive part. Issue 1 (October 2015) - Park, H S; Nguyen, T T
Abstract: Staking plastic is a new technology that used infrared light as the energy sources in order to assembly the heated plastic parts. In this work, the proposed method coupling between Finite Element Method (FEM), Response Surface Method (RSM), and Genetic Algorithm (GA) is employed to simulate and optimize the staking plastic process. An automotive part, namely Door Trim with polypropylene (PP) material is implemented by using the developed technology. The effects of three key process parameters, such as heating time, cooling time, and air flow rate on the mechanical behavior of the joint has been investigated. The simulation procedure based on DEFORM-3D multi-operation is conducted to integrate sub-process and obtain the numerical results. The optimum values, including heating time, cooling time, and air flow rate are 14 second, 14 second, and 60 (ft 3 /h), respectively. The optimizing results indicated that heating time is more contributed to the tensile force, following by cooling time and air flow rate. The correlation between simulation and experimental results indicates the effectiveness of the proposed method.